STRATEGI PEMOTIVASIAN DALAM PEMBELAJARAN TAHFIZH AL-QUR’AN - Supian, Supian; Vahlepi, Sahrizal; Sholiha, Mar’atun (Universitas Pendidikan Indonesia, 2019)
Abstact. This article examines motivating strategies in learning Tahfizh Al-Qur’an. The question in this study is what is the motivating strategies in learning Tahfizh Al-Qur’an applied at the Qur’an-Hadith School and the Integrated Islamic Boarding School Dar al-Masaleh Foundation, Jambi City. This type of research is qualitative research. Data is collected through participant observation, in-depth interviews, and documentation. To check the validity of the data, it is done by extending the participation, observation, and trigulation. The results of this study reveal that the strategy of motivation and learning tahfizh Al-Qur’an as follows: a) At first, arrange what you want to remember, b) Improve good communication between teachers and parents of students, c) Do not concentrate too much on memory material, d) Give prizes / sanctions, e) Give memorization targets, f) Create a pleasant atmosphere, and g) Hold student performances or take part in competitions. The supporting factors in learning Tahfizh Al-Qur’an are the motivation of the teacher and parents, conducive classroom atmosphere, the awareness of the students themselves and the good relationship between the teacher of tahfizh, parents and students. Otherwise, it will become obstacles.Abstrak. Artikel ini mengkaji strategi pemotivasian dalam pembelajaran Tahfizh Al-Qur’an. Pertanyaan dalam penelitian ini adalah bagaimana strategi pemotivasian dalam Pembelajaran Tahfizh Al-Qur’an di Sekolah Qur’an Hadits dan Sains Yayasan pesantren Terpadu Dar al-Masaleh Kota Jambi. Jenis penelitian ini adalah penelitian kualitatif. Pengumpulan data melalui metode observasi partisipan, wawancara mendalam, dan dokumentasi. Untuk mengecek keabsahan data, dilakukan dengan melakukan perpanjangan keikutsertaan, pengamatan, dan trigulasi. Hasil penelitian ini mengungkapkan bahwa strategi motivasi dan pembelajaran tahfizh Al-Qur’an sebagai berikut: a) Mengatur terlebih dahulu apa yang hendak diingat, b) Memperbaiki komunikasi yang baik antara guru dan orang tua siswa, c) Jangan memusatkan terlalu banyak bahan ingatan, d) Memberikan hadiah/sanksi, e) Memberikan target hafalan, f) Menciptakan suasana yang menyenangkan, g) Mengadakan pentas santri/siswa atau mengikuti kompetisi. Adapun faktor pendukung dalam pembelajaran Tahfizh Al-Qur’an adalah motivasi dari guru dan orang tua, suasana kelas yang kondusif, adanya kesadaran dari diri siswa dan adanya hubungan baik antara guru tahfizh, orang tua dan siswa. Jika sebaliknya maka akan menjadi faktor penghambat.